Electrochromic and electrofluorochromic bifunctional materials for dual-mode devices based on ladder-like polysilsesquioxanes containing triarylamine. (April 2020) - Zhang, Wei; Niu, Haiying; Yang, Caiyu; Wang, Yan; Lu, Qingyi; Zhang, Xu; Niu, Haijun; Zhao, Ping; Wang, Wen
Abstract: The display devices of the future will tend to be multifunctional, and the dual-mode device for emission and coloration satisfies the requirements of practical applications. We synthesized materials with electrochromic (EC) and electrofluorochromic (EFC) properties through the combination of triarylamine (TAA) and ladder-like polysilsesquioxanes (LPSQs). The ladder-like structure was confirmed by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and 29 Si-NMR techniques. These polymers exhibit up to 37.3% fluorescence (PL) quantum efficiency ( Ф PL ) and show strong solid-state fluorescence because TAA groups are effectively isolated in ladder-like backbone in LPSQs. The TAA-LPSQs films exhibit reversible change from colorless of bleached state to blue or green of oxidized state. Among them, the optical contrast of the MPA-LPSQ film synthesized from 1-(4-(bis(4-methoxyphenyl)amino)phenyl)-3-(3-(triethoxysilyl)propyl)urea is as high as 83.0% at 787 nm, which shows excellent cycle stability over 1000 s. Unique structure and good electrochemical activity of TAA-LPSQs make them promising materials for dual-mode device. The EC/EFC device (ECD/EFCD) was assembled using MPA-LPSQ as an active layer which showed good performance. In addition, TAA-LPSQs exhibit excellent sensitivity to 2, 4, 6-trinitrotoluene (TNT) and 2, 4, 6-trinitrophenol (TNP) detection, so these materials can also be applied as highly sensitive chemosensor for explosives. Graphical abstract: Image 1 Highlights: Ladder-like polysilsesquioxanes with side chain triarylamines were synthesized. MPA-LPSQ film exhibited 83.0% optical contrast at 787 nm. The polymers show simultaneous electrochromic, electrofluorochromic.